Perspectives of Immigrants and Native Dutch on Antibiotic Use: A Qualitative Study - Dominique L. A. Lescure; Alike W. van der Velden; Natascha Huijser van Reenen; Jan Hendrik Richardus; Helene A. C. M. Voeten (MDPI AG, 2022)
Immigrants constitute large proportions of the population in many high-income countries. Knowledge about their perceptions of antibiotics, in comparison to native populations, is limited. We explored these perceptions by organizing nine homogeneous focus group discussions (FGDs) with first-generation immigrant and native Dutch participants (N = 64) from Rotterdam and Utrecht, who were recruited with the assistance of immigrant (community support) organizations. The FGDs were audio-recorded and transcribed verbatim. Inductive thematic analyses were performed with the qualitative analysis software Atlas.ti, using open and axial coding. We did not find noteworthy differences between immigrants and native Dutch participants; all participants had an overall reluctant attitude towards antibiotics. Within-group differences were larger than between-group differences. In each FGD there were, for instance, participants who adopted an assertive stance in order to receive antibiotics, who had low antibiotic-related knowledge, or who used antibiotics incorrectly. Native Dutch participants expressed similar difficulties as immigrant participants in the communication with their GP, which mainly related to time constraints. Immigrants who encountered language barriers experienced even greater communicational difficulties and reported that they often feel embarrassed and refrain from asking questions. To stimulate more prudent use of antibiotics, more attention is needed for supportive multilingual patient materials. In addition, GPs need to adjust their information, guidance, and communication for the individual's needs, regardless of the patient's migration background.